Determination of reliability, validity and norm of California critical thinking skills test, form B - A Davoodi (Babol University of Medical Sciences, 2003)
Background and Objective: The purpose of this research was to investigate the reliability, validity and norm of CCTST F.S. The California critical thinking skills test (CCTST) contains 34 multi-choice questions with a correct answer in the five critical thinking (CT) cognitive skills domain. Methods: This research is a methodological study, which has been performed on 405 BSN nursing students of Tehran medical sciences colleagues that were selected on the base of stratified random sampling method. In order to determine the face and content validity the test was translated and edited by Persian and English language professors and researchers. Also, it was confirmed on the basis of medical education and psychology professor’s judgment. CCTST reliability was determined with internal consistency and use of KR-20. For investigation of construct validity of the test after performed factor analysis, it was also used the internal consistency and group difference. In related to test scores normally on the base of scores frequency distribution tables, scores percentile norm was investigated. Findings: The test reliable coefficient was 0.62%. Factor analysis indicated that CCTST has been formed from 5 factors (Elements) namely: Analysis, evaluation, inference, inductive and deductive reasoning. Internal consistency method showed that all subscales have been high and positive correlation with total test score. Group difference method between nursing and philosophy students (n=50) indicated that there was a significant difference between nursing and philosophy students’ scores (P=0.0001). Scores percentiles norm also showed that percentile of 5, 50, 95 scores related to 6, 11 and 17 raw score, respectively. Conclusion: The results revealed that the questions test is enough reliable as a research tool and correlated with test theoretical structure, and all subscales measured a single construct (Critical thinking) and be able to distinguish the persons with different level’s CT.